EFETIVITAS METODE INQUIRY LEARNING DALAM MENINGKATKAN KEMAMPUAN ANALISIS PADA MATERI IPA SISWA KELAS III SDN TLOGOANGUNG - Kiky Chandra Silvia Anggraini (Universitas Islam Lamongan, 2019)
This study aims to examine the use of inquiry methods for the ability of student analysis. Based on the M Problem that is faced by the teachers of the school base on learning of science. The method is carried out by conducting pre-experiment by conducting a pretest and posttest during the research. The instrument used in the form of a written test and for data analysis using paired sample t test with the help of SPSS 25. After paired test t sample test is known if the significance value is 0.00 or smaller than 0.005. which means Ha was accepted and Ho rejected